Electrical stimulation of the ventral tegmental area evokes sleep‐like state transitions under urethane anaesthesia in the rat medial prefrontal cortex via dopamine D1‐like receptors. (24th February 2020) - Gretenkord, Sabine; Olthof, Bas M. J.; Stylianou, Myrto; Rees, Adrian; Gartside, Sarah E.; LeBeau, Fiona E. N.
Abstract: The role of dopamine in regulating sleep‐state transitions during, both natural sleep and under anaesthesia, is still unclear. Recording in vivo in the rat mPFC under urethane anaesthesia, we observed predominantly slow wave activity (SWA) of <1 Hz in the local field potential interrupted by occasional spontaneous transitions to a low‐amplitude‐fast (LAF) pattern of activity. During periods of SWA, transitions to LAF activity could be rapidly and consistently evoked by electrical stimulation of the ventral tegmental area (VTA). Spontaneous LAF activity, and that evoked by stimulation of the VTA, consisted of fast oscillations similar to those seen in the rapid eye movement (REM)‐like sleep state. Spontaneous and VTA stimulation‐evoked LAF activity occurred simultaneously along the dorsoventral extent of all mPFC subregions. Evoked LAF activity depended on VTA stimulation current and could be elicited using either regular (25–50 Hz) or burst stimulation patterns and was reproducible upon repeated stimulation. Simultaneous extracellular single‐unit recordings showed that during SWA, presumed pyramidal cells fired phasically and almost exclusively on the Up state, while during both spontaneous and VTA‐evoked LAF activity, they fired tonically. The transition to LAF activity evoked by VTA stimulation depended on dopamine D1 ‐like receptor activation as it was almost completely blocked by systemic administration of the D1 ‐like receptor antagonist SCH23390. Overall, our data demonstrate that activation of dopamine D1 ‐like receptors in the mPFC is important for regulating sleep‐like state transitions. Abstract : Under urethane anaesthesia, activity in the PFC spontaneously switches between slow wave activity and rapid eye movement (REM)‐like, low‐amplitude fast (LAF) oscillations. Electrical stimulation of the ventral tegmental area (VTA) evokes LAF in the PFC. Transition to LAF evoked by stimulation of the VTA is blocked by systemic SCH23390, a D1/5 antagonist. Dopamine, acting via D1/5 receptors, contributes to SWA/LAF transitions demonstrating a new role for dopamine in sleep‐like state transitions.